Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/jps.24272
|View full text |Cite
|
Sign up to set email alerts
|

Routes of Administration and Dose Optimization of Soluble Antigen Arrays in Mice with Experimental Autoimmune Encephalomyelitis

Abstract: Soluble Antigen Arrays (SAgAs) were developed for treating mice with experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis. SAgAs are composed of hyaluronan with grafted EAE antigen and LABL peptide (a ligand of ICAM-1). SAgA dose was tested by varying injection volume, SAgA concentration, and administration schedule. Routes of administration were explored to determine the efficacy of SAgAs when injected intramuscularly, subcutaneously, intraperitoneally, intravenously, or instil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 26 publications
(55 reference statements)
0
31
0
Order By: Relevance
“…Multiple sclerosis (MS) is an autoimmune disease in which immune cells attack and degrade the myelin sheath surrounding neurons, thus interrupting the transmission of electrical signals 3,4,10,11 . Many of the current therapies approved for MS focus on treating inflammation or neurological symptoms such as loss of balance, degrees of paralysis, and a loss of coordination.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple sclerosis (MS) is an autoimmune disease in which immune cells attack and degrade the myelin sheath surrounding neurons, thus interrupting the transmission of electrical signals 3,4,10,11 . Many of the current therapies approved for MS focus on treating inflammation or neurological symptoms such as loss of balance, degrees of paralysis, and a loss of coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the current therapies approved for MS focus on treating inflammation or neurological symptoms such as loss of balance, degrees of paralysis, and a loss of coordination. Recently, researchers have aimed to correct the underlying immune response using ASIT 4,12,13 . There are different forms of this disease: secondary progressive, primary progressive, progressive relapsing, and relapsing-remitting, the latter of which affects a majority of patients, approximately 80% 4,10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to BPI molecules, the development of soluble antigen arrays (SAgAs; Figure 5) was inspired by a combination of the BPI concept and Dintzis’ rules, which have been shown to induce immune stimulation or tolerance [100106]. Dintzis’ rules indicated that induced immune responses are influenced by particle size, solubility, flexibility, antigen valency, spacing, and binding avidity.…”
Section: E Peptide-particle and Peptide-polymer Conjugatesmentioning
confidence: 99%